The Influence of Work Discipline and Work Environment on Employee Performance at Palma Shop Majalengka - Utomo, Sudibyo Budi (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Palma Shop Majalengka is a business entity operating in the field clothing retail trade. Located on Jl. Raya Heuleut-Weragati, Tanjungsari Village Leuwimunding District, Majalengka Regency. This research aims to determine the influence of work discipline and work environment on employee performance. This research uses descriptive and verification methods with an approach quantitative. The population is 30 employees, the sampling technique is technical census so that the sample totals 30 employees. Data collection technique using the questionnaire method. Data analysis is carried out using analysis descriptive and verification in the form of multiple regression coefficients, coefficients of determination and hypothesis testing. The results of this research are that work discipline has a positive effect and significant impact on employee performance, the work environment has a positive effect and significant impact on employee performance and work discipline and work environment simultaneously have a positive and significant impact on employee performance.